Sedentariness and overweight in relation to mortality in sub-Saharan Africa. A mediation analysis based on the World Health Organization-Global Health Observatory data repository - Sunday Onagbiye; Hannah Ricci; Petra Bester; Cristian Ricci (AOSIS, 2023)
Background: Globally, noncommunicable diseases (NCDs) have been continuously reported to be the number one leading cause of reduced life expectancy and poor life quality and have thus become a major public health concern. Objective: This study aimed to investigate the complex mediation analysis between physical inactivity and overweight in relation to mortality. Methods: The study is based on public data collected by the Global Health Observatory of the World Health Organization. Results: We showed that the median early mortality attributable to NCDs during the period 2016-2019 in both men and women was 23.2% (5th to 95th range=17.2, 35.6) while that in men alone was 25.1% (16.5, 45.7) and that of women alone was 22.0% (17.0, 27.9). When considering regional early NCDs mortality for both men and women, a systematically high median was observed in Southern Africa [28.7% (22.2, 43.8)] and a low median in Eastern Africa [21.1% (17.15, 27.3)]. The analysis of the overall relation between physical inactivity, overweight and early mortality due to NCDs revealed a statistical significance of the direct association between physical inactivity and early mortality due to NCDs. Conclusion: Our findings revealed three main epidemiological and public health concerns. First, early mortality attributable to NCDs in a range of about 20 to 30% across the sub-Saharan African regions for both sexes was observed. Second, there was a direct effect between physical inactivity and early NCDs mortality as well as the indirect effect mediated by overweight. Finally, a percentage point decrease in physical inactivity prevalence and overweight could effectively generate a reduction in mortality due to NCDs. Future studies are needed to confirm the scientific evidence observed in this study. Such studies should be based on observation of individual subjects, adopt a longitudinal design, and collect information that evaluates the complex relationship between physical inactivity and early NCDs mortality, along with the role of overweight as a possible mediator.